2019
DOI: 10.2147/dmso.s228591
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differential Expression of Human N-Alpha-Acetyltransferase 40 (hNAA40), Nicotinamide Phosphoribosyltransferase (NAMPT) and Sirtuin-1 (SIRT-1) Pathway in Obesity and T2DM: Modulation by Metformin and Macronutrient Intake</p>

Abstract: Background: Interactions between environmental factors, such as diet and lifestyle, and metabolic pathways are pivotal in understanding aging mechanisms. hNAA40, Nicotinamide phosphoribosyltransferase (NAMPT), and NAD-dependent protein deacetylase sirtuin-1 (SIRT-1) have been shown to exert important biological processes, including stress response and aging. Methods: hNAA40, NAMPT, and SIRT-1 mRNA expression in peripheral blood mononuclear cells (PBMC) were quantitated in 30 lean adult volunteers of normal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In our study, SIRT1 levels of Wistar proved to be unusually low, even seemingly lower than that of Goto control group, although the difference did not reach the level of statistical significance. According to other scientific articles, calorie restriction increases SIRT1 concentrations [38] while in contrast overweight and obesity is associated with SIRT1 down-regulation [39,40], which might have been the reason in our experiment for the lower than usual SIRT1 expression in case of the Wistar rats that produced significant weight gain during the study.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, SIRT1 levels of Wistar proved to be unusually low, even seemingly lower than that of Goto control group, although the difference did not reach the level of statistical significance. According to other scientific articles, calorie restriction increases SIRT1 concentrations [38] while in contrast overweight and obesity is associated with SIRT1 down-regulation [39,40], which might have been the reason in our experiment for the lower than usual SIRT1 expression in case of the Wistar rats that produced significant weight gain during the study.…”
Section: Discussionmentioning
confidence: 70%
“…The results of the present study indicate that NAMPT serum levels decrease considerably in the group without complications compared to all other groups and controls. Similarly, Alshahrani et al (2019) stated that NAMPT expression is reduced in obese patients with T2DM, and metformin treatment reverts NAMPT expression to normal levels. However, Kieswich et al (2016) showed that serum levels increased for monomeric eNAMPT in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…PCA analysis indicated sirtuin system gene expression patterns were not ascribed by menopausal status or the meal consumed except for reduced NAMPT in post‐menopausal women. NAMPT is involved in many important biological processes, including metabolism, stress response, and aging [ 39 ] (Figure S2, Supporting Information). However, gene expression measures used as input for PCA revealed stratification of the cohort into two subgroups, designated subgroups A and B. Subgroup A had higher expression of several sirtuin system gene targets compared to subgroup B. Gene expression profiles characterizing subgroup A were higher levels of NMRK1, SIRT5, NADSYN1, NMNAT1, SIRT6, PPIB, SIRT1, SIRT2, ABCA1, SIRT3, NAMPT, and PARP1 expression, and lower levels of NMRK2 and NMNAT2 .…”
Section: Discussionmentioning
confidence: 99%